Fal – Fortune Telling from Chalil Juzefovich’s Tefsir (19th Century) - Miškinienė, Galina (Lietuvos istorijos studijos, 2023)
At the junction of the 20th–21st centuries more and more attention was being paid to the written heritage of Lithuanian Tatars. From 1997 to 2020 seven catalogues of Lithuanian Tatars manuscripts were published. These catalogues describe the Lithuanian Tatars manuscripts, which are kept in state institutions, museums, archives, as well as in private collections of various countries. The larg- est collections of manuscripts are stored in Belarus and Lithuania. The emergence of such catalogues is an excellent basis for further comparative studies. In 2020 the author of this article managed to get acquainted with a new collection of manuscripts stored in a private collection. Five manuscripts were reviewed and analysed during this research. All of them perfectly represent the main genres of Lithuanian Tatars manuscripts heritage – kitabs, semi-kitabs, hamails, and tefsirs. The manuscripts are dated from the end of the 19th century to the beginning of the 20th century. Five manuscripts from this collection were presented in the article “Lithuanian Tatar Manuscripts Written in Arabic Script from the Private Collection: New Discoveries” (2020). So far, the content of only one manuscript has been described in a published article. Starting with the catalogue of Lithua- nian Tatar manuscripts written in Arabic script (2005), in which the compilers drew attention to the content of the manuscripts, other catalogues (2011, 2015, 2020) were published according to the same principles – revealing the content of the manuscript. An opportunity to undertake textological analysis of texts opened for researchers. The folklore material from some manuscripts makes a system of incantations, healing spells, and protective rites that were popular not only among the Muslim community, but also among Christians and Jews. This system is closely related to beliefs and superstitions, the origins of which are found in the universal Muslim culture adopted by the Turks. Kitabs and chamails are abound of astrological, calendrical and magical texts. Texts about auspicious and inauspicious days, dreamers and fals (fortune-telling) attract the attention of scholars. In this article, we present a fal that we have found in the tefsir (sufra) written by Chalil Juzefovich. This tefsir is dated from the 19th century. Although the fortune-telling text, which is being described for the first time, has no analogues in other manuscripts, it will provide excellent material for further comparative studies. It is much more difficult to determine the source(s) of such texts, as they were very popular in folk culture, may have had a number of variants and a wide circle of distribution. However, with each newly discovered and decoded text, we reveal a layer of Lithuanian Tatar manuscripts.